Development of biosensor probe for detection of Malachite Green and Leuco-Malachite Green for application in fishery industry - Ahmad Puat, Nurul Hidayah (2013)
The use of Malachite Green (MG) as an anti-fungal and anti-bacterial in the aquaculture industry has obtained attention in food safety. MG and its metabolite Leuco-Malachite Green (LMG) are highly toxic to aquatic environment and harmful to human health through daily consumption and it becomes more dangerous when accumulated in fish tissues. At present, the minimum required performance limits (MRPLs) for total MG (MG and LMG) concentration is 2 μgkg-1 or 2 ppb. Hence, the simple, rapid, sensitive and portable biosensor is really needed. The aim of this research is to study the chemical inhibition of Butyrylcholinesterase enzyme (BuChE) by total MG in the presence of 0.3 mM Butyrylthiocholine iodide substrate (BTCi) for MG biosensor development. The MG biosensor has developed for total MG detection in fishes especially the tilapia and has validated by using the LC-MS/MS method. This electrochemical study has done by using screen-printed carbon electrode (SPCE) and the inhibition study has done by using free and immobilized enzyme. Then, it has characterized and analyzed using cyclic voltammetry (CV) and chrono-amperometry (CM). The supporting electrolyte, pH, set potential, scan rate and response range includes enzyme loading, polymer concentration, incubation and response time of the MG biosensor has optimized electrochemically. Meanwhile, the reproducibility, repeatability, operational stability and storage stability included cross reactivity has carried out. Finally, the developed MG biosensor method was validated with the LC-MS/MS method using real fish samples including the recovery study. In this study, 4UmL-1 BuChE enzyme (C1057) has used and the CV analysis was carried out as a preliminary study. The reproducibility of the SPCE was characterized electrochemically against potassium hexacyanoferrate (II) trihydrate and 93.65 % active surface areas of carbon working electrode were achieved. BuChE enzyme has incorporated within 0.08M pyrrole monomer during the electro-polymerization process at 0.1 V amperometrically for 20 minutes, which enzyme has entrapped within the thin films of polypyrrole (PPy). The total MG (MG and LMG) has determined by measuring the current using amperometric technique at 0.4 V for 100 s using 0.1 M phosphate buffer at pH 8.0. This analysis needs five minutes of incubation time for enzyme-substrate reaction and inhibition before measurement, and it may get up to 78 % inhibition at 2 ppb total MG. A linear standard curve of total MG has developed (0.25 ppb to 10 ppb) based on the current measurement (μA) using standard solution (Y = - 0.9113x + 10.84, R2 = 0.9445), which has good reproducibility and operational stability until five measurements. Instead of that, the enzyme activity has reduced (repeatability) slowly after the third measurement. However, the MG biosensor probe is able to re-use after treated with the pyridine-2-aldomine (PAM-2) activator. The shelf life of the MG biosensor took more than six months with 20 % protein or enzyme loss. The total MG also showed the higher inhibition (48 %) at 2 ppb compared to other triphenylmethane dyes. This MG biosensor method has validated using the LC-MS/MS method with a regression value of 0.9262 (correlation graph) upon ten unknown samples with recoveries valuing more than 60 % of spiked sample.